Estudio de la imagen corporativa y la reputación online en la red social Facebook de la Empresa Moderna de Alimentos, período julio-diciembre 2021 - Escobar Zambrano, Melanie Nicole (2024)
ABSTRACT: The purpose of this research work is to study the corporate image and online reputation of Empresa Moderna de Alimentos in the social network Facebook, period July-December 2021. The results obtained are based on interviews with an expert in online reputation and a community manager who provided their knowledge for this work. From the content analysis method, it was possible to achieve a better observation of the object of research, the study of this project is qualitative-quantitative, because it analyzes characteristics of the content of each publication made on the fanpage of the company such as: lead, keywords, hashtag, links, emojis or tags used, which in turn will be considered what type of publication has been made by the company in the given time of study. This allowed verifying the content present on the official Facebook page of the company Moderna de Alimentos, which allowed the researcher to perform a complete analysis of each publication. From this analysis, the research can be continued to determine the content analysis matrix to be used and seek input from experts in the field of communication and online reputation to support the findings of this study.